Analysis of Service Quality to Customer Satisfaction with CSI and Servqual Methods - Anang Ahmad Ainul Yahya; Rio Candra Pratama; Ardana Putri Farahdiansari (Journal of Information System, Technology and Engineering, 2023)
AHASS Jaya Sakti is a workshop service that provides services to vehicles with Honda motorbikes. AHASS Jaya Sakti can be found on Jl. Jaksa Agung Suprapto No.160, Bojonegoro. Competition in the automotive industry has become so intense that it is no longer limited to product sales, but has begun to extend to the creation of differentiation and competitive advantage through the provision of services. The method used in this study is to use the Service Quality (Servqual) and Customer Satisfaction Index (CSI) methods. The results of data processing carried out at the AHHAS Jaya Sakti workshop as a whole meet customer expectations with a value of 0.10044. This is evidenced by the Customer Satisfaction Index (CSI) value of 83%, which indicates that AHHAS workshop customers are very satisfied with the services provided. Then there are several attributes that have a negative gap value in AHHAS workshop services, namely the reliability dimension of attribute X6 with a gap value of -0.014, attribute X8 with a gap value of -0.06, attribute X9 with a gap value of -0.03, attribute X10 with a gap value of -0.11, the responsiveness dimension of attribute X11 with a gap value of -0.03, the guarantee dimension of attribute X17 with a gap value of -0.1, attribute X18 with a gap value of -0.07, and finally the empathy dimension of attribute X22 with a gap value of -0.03, attribute X24 with a gap value of -0.029.